Detection of Bacterial Blight Resistance Gene in Some Cultivated Rice Varieties Using Gene Based Molecular Markers (Journal of Science and Technology Research, 2026)
Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. Oryzae, known as Xoo in short, stands as one of the oldest and most destructive diseases affecting rice in Bangladesh. Despite this longstanding challenge, developing highly resistant rice varieties against this disease remains elusive. To address this gap, we conducted a study examining 15 cultivated rice varieties to assess their disease reaction status against a highly virulent strain of Xoo. Using five sequence-tagged site (STS) markers that correspond to the Xa4, Xa5, Xa13, Xa21, and Xa23 genes, our investigation aimed to identify potential candidate resistant (R) genes that may be responsible for the resistant reaction. After the pathogenicity test, the results revealed 1 cultivated rice variety (BRRI dhan101) showed resistant reaction, 1 as moderately resistant, 2 as moderately susceptible, 8 as susceptible, and 3 as highly susceptible. Further molecular analysis of the 15 rice varieties revealed that 9 carried the Xa4 gene, 1 carried the Xa5 gene, and 1 carried the Xa21 gene. Interestingly, various gene combinations, ranging from 1 to 2 genes, were observed among the rice varieties, with 2 varieties carrying 2-gene combinations and 13 carrying single genes. Notably, the BRRI dhan101 rice variety, which exhibited resistance, harbored the most effective combination of Xa4 and Xa21 genes against the Xoo strain. The findings of this study hold promise in enriching and diversifying the rice gene pool, offering potential candidates for the development of durable resistant varieties against BLB in Bangladesh.J. of Sci. and Tech. Res. 6(2): 121-129, 2025